(untitled) (KYAMC Journal, 2013)
Background: Increased body mass index (BMI) is known to be related to ischaemic heart disease (IHD) in populations where many are overweight (BMI ? 25 kg/m2) or obese (BMI ? 30). Substantial uncertainty remains, however, about the relationship between BMI and severity of Coronary artery disease. Methods and Results: Total 152 patients undergoing coronary angiography for clinical indication (eg; stable angina, unstable angina, STEMI, NSTEMI). Among them 88.15% male and 11.84% female.6.57% were under weight, 69.07% were normal weight, 20.39% were over weight and 3.94% were obese or morbid obese. Normal & minimal coronary artery disease more common in under weight & normal weight patient ( 60% in underweight patient, 21.88% in normal weight patient compare to 16.12% in over weight & obese person). Tripple Vessel disease are more common in over weight and obese person (45.16% in over weight and 50% in obese person compare to 10% in under weight and 33.33% in nonmal weight person). Conclusion: In patients with established Ischemic heart disease, Increase BMI was associated with increase number of coronary lesion ( doable and tripple vessel disease more common in over weight and obese person). DOI: http://dx.doi.org/10.3329/kyamcj.v1i2.13312 KYAMC Journal Vol.1(2) 2011 pp.39-42